Pendekatan Haptic Visuality pada Konstruksi Visual Film Burung Dara - Guntur Tri Wasono; Muhammad Zamroni; Fajar Aji (Program Studi Film dan Televisi Universitas Jember, 2022)
Eros love is one of love that is identic with the sensation of arousal and sexual desire in the pattern of teenage romance. The content of love that is attached to the emotions of actors and sensation of desire makes the author take on the major cinematographer in film Burung Dara. Burung Dara tells the story of a couple teenage who having relationship beyond the bounds of the norm. The author uses a haptic visuality approach combined with emotional rhythm editing techniques to amplify emotions and give a touch-like sensation to the visuals of teenage love through a 27-minute film with a drama genre.